“Political theology” of emperor Alexander I: ideas, representations, practice - Andrei Andreev (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
In 1815, the Russian Emperor Alexander I formulated the principles of a new world order, which was supposed to ensure long-term and stable peace after two decades of continuous wars in Europe. This project, called the Holy Alliance, was based not so much on foreign policy as on religious grounds. This article examines in detail the set of ideas put forward by Alexander I from the point of view of political theology. The religious motives that moved the Russian emperor are shown, determined by the peculiarities of his spiritual life. The rhetoric of the Holy Union, its basic concepts related to the Christian doctrine are analyzed. Special attention is paid to the representations of the Holy Union in the public sphere, namely, the solemn God services designed to prove the unity and "brotherhood in Christ" of the monarchs of Europe and their peoples. At the same time, the study demonstrated how significant the image of the enemy, embodied as “revolution”, played in the justification of the Holy Alliance within the framework of political theology. The concept of revolution was extremely generalized by Alexander I and interpreted as a manifestation of universal evil. This lead to the doctrine of interventions under the auspices of the Holy Alliance in the country affected by the revolution, which in turn provoked new bloodshed. An analysis of the accumulated contradictions made it possible to draw a conclusion about the reasons for the fading of Alexander’s interest in the constructions of political theology in the last years of his reign.